2023
DOI: 10.1039/d3se00194f
|View full text |Cite
|
Sign up to set email alerts
|

Solar energy driven C–C bond cleavage in a lignin model compound with a D–π–A organic dye-sensitized photoanode

Abstract: Chemoselective C–C bond cleavage remains a challenge in organic synthesis and for the degradation of polymers because of the relatively high bond dissociation energy of C–C σ-bonds at room temperature....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Also, the chemical shift at around δH/δC 5.93/106.16 ppm appeared after the oxidative reaction, indicating the cleavage product P1 . ,, The peaks at δH/δC 9.67/200.87 (D a ) and δH/δC 4.63/83.48 (D b ) were assigned to the C/H correlations of C a /H a and C b /H b , respectively, of product derived from G unit P2 . In the reaction at pH 5, the contours at δH/δC 5.42/80.44 in the aliphatic region and δH/δC 7.33/105.73 in the aromatic region correspond to the C/H correlations of C β /H β and C 2/6 /H 2/6 , respectively, from the oxidized C α -ketone ( P4 ) structure (A ox ). , Based on the above results and aforementioned studies, we propose a pH-dependent breakdown of β-O-4 aryl ether bonds in phenolic LMC via enzymatic oxidation catalyzed by PcLiP01, as shown in Figure S6. When the cationic radical Int 1 is produced through the SET from S1 to Cpd I/II , deprotonation occurs due to the very low p K a of phenol radical cations (p K a (ArOH) •+ ≈ −2.0), , leading to the prevalence of phenoxy radicals 1a compared to radical cations.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Also, the chemical shift at around δH/δC 5.93/106.16 ppm appeared after the oxidative reaction, indicating the cleavage product P1 . ,, The peaks at δH/δC 9.67/200.87 (D a ) and δH/δC 4.63/83.48 (D b ) were assigned to the C/H correlations of C a /H a and C b /H b , respectively, of product derived from G unit P2 . In the reaction at pH 5, the contours at δH/δC 5.42/80.44 in the aliphatic region and δH/δC 7.33/105.73 in the aromatic region correspond to the C/H correlations of C β /H β and C 2/6 /H 2/6 , respectively, from the oxidized C α -ketone ( P4 ) structure (A ox ). , Based on the above results and aforementioned studies, we propose a pH-dependent breakdown of β-O-4 aryl ether bonds in phenolic LMC via enzymatic oxidation catalyzed by PcLiP01, as shown in Figure S6. When the cationic radical Int 1 is produced through the SET from S1 to Cpd I/II , deprotonation occurs due to the very low p K a of phenol radical cations (p K a (ArOH) •+ ≈ −2.0), , leading to the prevalence of phenoxy radicals 1a compared to radical cations.…”
Section: Resultsmentioning
confidence: 98%
“…Our recent study reported the first approach, photocatalytic chemoselective cleavage of the C­(aryl)–C­(sp3) σ-bond in a phenolic lignin model compound (LMC) at room temperature, by using a photoelectrocatalytic (PEC) process (Figure b). This system yielded excellent selectivity (>90%) for C–C bond cleavage of a phenolic LMC at room temperature in the presence of aminoxyl mediators resulting in producing a value-added aromatic chemical, 2,6-dimethoxybenzoquinone (DMBQ) . However, this work has been limited to studying a relatively simple phenolic LMC that lacks the additional electron-rich moieties in real lignin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the similarities in the mechanism, including the light absorption and ion/electron transport, the success of the ideal device design for solar hydrogen production can be expanded toward other types of "articial leaf," such as producing chemical fuels from solar energy via CO 2 reduction, 46 PEC ammonia synthesis, 47 and biomass valorisation. 48 In summary, to fabricate membrane-embedded PEC watersplitting devices, three key characteristics must be satised:…”
Section: Membrane-embedded Pec Water-splitting Devicesmentioning
confidence: 99%
“…For example, the most recent one is on the cleavage of C–C/C–O bonds in lignin using dye-sensitized photoelectrosynthetic solar cells. This method presents a promising direction for the sustainable production of chemicals based on lignin [ 111 , 112 ].…”
Section: Lignin-based Networkmentioning
confidence: 99%